Production and price behaviour of potato, (Solanum tuberosum) in Khasi hills region of Meghalaya - GOSWAMI, S N (The Indian Journal of Agricultural Sciences, 2013)
A study was carried out during 1991 to study cyclic variation in the production and price of potato (Solanum tuherosum 1.) in the Khasi hills. Data on production and wholesale prices of potato for the study area Were collcetcd for 24 years (1964-65 to 1987-88). Fourier analysis was done to compute the Fourier coefficients for finding out the hypothesized length of the cycle. The correlogram analysis helped in distinguishing between 3 types of oscillatory series, viz moving average, auto-regressive schemes and harmonic terms. The analysis revealed that regular cycles of a given length appeared both in production and prices. The production and price cycles did not persist in uniform manner. The amplitude of the swingin the price cycle was larger than that in the production cycle. The variation in production and price of potato was lower in recent years (1986--87 and 1987-88) than in early years (1964-65, 1965-66 and 1966-67). The lesser variation in recent years might be due to the improvement in varieties. package of practices and marketing systems. The appropriate, timely, well-designed price policies may be the solution to stabilize price and increase the level of production.